Wading Through Jerusalem’s Garbage: Chronology, Function, and Formation Process of the Pottery Assemblage of the City’s Early Roman Landfill - Machline, Hélène; Gadot, Yuval (Journal of Hellenistic Pottery and Material Culture, 2017)
Most scholars would agree that garbage constitutes a large portion of the source of materials discovered in archaeological excavations. Official garbage disposal areas (landfill) from the past, however, have rarely been studied by archaeological methods. In this article, we wish to present a unique pottery assemblage that originates from what was minimally a 7 m thick accumulation of alternating soil layers that we interpret as Jerusalem’s official landfill during the Early Roman period.